Impact of Positive Feedback, Based on a Humanistic Approach, on the Learning Process of a 10th Grade EFL Course at a Public High School in the East of Antioquia (2021)
ABSTRACT : This project aimed at identifying the impact of positive feedback, implemented through a humanistic approach, on the learning process of 10th graders. I carried out the study in a public urban institution from El Carmen de Viboral – Antioquia with 46 students. The project included two stages: The first stage consisted of observations to the CT to explore and know the context of the classes. The second stage was the implementation itself, in which I carried out a project for several weeks consisting of providing positive feedback. The data collection instruments comprised the teacher’s journal, a questionnaire to the students, an interview with the CT, and a focus group. Findings revealed that students tend to feel more motivated after encouraging comments. Besides, students appreciated the constant accompaniment from the teacher and the intention to include them all in the learning process. Nevertheless, a challenge of the project was the number of students, which could hinder the inclusion of each student's way of being and learning.